Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

Association between cagemate number and risk of death in mice: a time-varying covariate analysis using Cox frailty models - Thirupathi R. Mokalla; Erik S. Parker; Daniel L. Smith; Luis-Enrique Becerra-Garcia; Olivia C. Robertson; Deependra K. Thapa; Mounika Kandukuri; Bret M. Rust; David B. Allison (GeroScience, 2026)
Social housing is desirable for the health and well-being of laboratory mice, as social interactions with conspecifics influence both behavioral and physiological outcomes. Although group housing benefits social species, it can introduce variability in mortality outcomes, and raise welfare concerns, particularly with the emergence of aggression or fluctuating cage densities. Despite this, few studies have evaluated how changes in the number of living cagemates over time are associated with survival, particularly in a sex-specific manner. We analyzed data from the National Institute on Aging’s Interventions Testing Program (ITP; n = 2635 UM-HET3 mice), across three research sites to assess whether housing density influenced longevity differently in male and female mice. Mice were housed in same-sex cages (median = 3 per cage) without reassignment after cagemate death. We applied Cox frailty models incorporating nested random effects for cage and site, with fixed effects for sex, treatment, and time-varying number of living cagemates to estimate hazard ratios, which allowed us to assess the instantaneous risk of death associated with changes in cagemate number. Results showed a significant main effect of the number of living cagemates on mortality and a significant interaction between sex and cagemate count, indicating sex-specific responses. Female mice exhibited a pronounced increase in mortality rate as cage density declined, suggesting a potential role of social buffering in longevity. These findings emphasize the importance of considering social housing dynamics, particularly for female mice, in both experimental design and animal welfare protocols. Graphical Abstract

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

P18-17 No Evidence of E-Cigarette Aerosol-Induced Cisplatin Resistance in Head and Neck Cancer Cells: Findings from the Replica International Study Group - G. Carota; R. Emma; K. Partsinevelos; S. Rust; A. Sun; A. Giordano; V. Volarevic; R. Lesmana; H. Goenawan; M.I. Barliana; A. Arsenijevic; N. Kastratovic; et al. (Toxicology Letters, 2025)

P01-33 Toxicity induced by cigarette smoke and electronic cigarette aerosols - K. Partsinevelos; R. Emma; A. Distefano; G. Carota; S. Rust; R. Pulvirenti; D. Campagna; R. Polosa; M. Caruso; G. Li Volti (Toxicology Letters, 2024)

Large silicic magma bodies and very large magnitude explosive eruptions - R. S. J. Sparks; J. D. Blundy; K. V. Cashman; M. Jackson; A. Rust; C. J. N. Wilson (Bulletin of Volcanology, 2022)
Over the last 20 years, new concepts have emerged into understanding the processes that lead to build up to large silicic explosive eruptions based on integration of geophysical, geochemical, petrological, geochronological and dynamical modelling. Silicic melts are generated within magma systems extending throughout the crust by segregation from mushy zones. Segregated melt layers become unstable and can assemble into ephemeral upper crustal magma chambers rapidly prior to eruption. In the next 10 years, we can expect major advances in dynamical models as well as in analytical and geophysical methods, which need to be underpinned in field research.

MeMoVolc consensual document: a review of cross-disciplinary approaches to characterizing small explosive magmatic eruptions - L. Gurioli; D. Andronico; P. Bachelery; H. Balcone-Boissard; J. Battaglia; G. Boudon; A. Burgisser; M. R. Burton; K. Cashman; S. Cichy; R. Cioni; A. Di Muro; et al. (Bulletin of Volcanology, 2015)

Generation of the Sotos syndrome deletion in mice - Anna M. Migdalska; Louise van der Weyden; Ozama Ismail; Alistair G. Rust; Mamunur Rashid; Jacqueline K. White; Gabriela Sánchez-Andrade; James R. Lupski; Darren W. Logan; Mark J. Arends; David J. Adams (Mammalian Genome, 2012)

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Bioencapsulation of erythromycin using adult brine shrimp, Artemia franciscana (Latreille) - T J. Majack; M B. Rust; K C. Massee; . G. W. Kissil; R W. Hardy; M E. Peterson (Journal of Fish Diseases, 2000)
Live adult brine shrimp, Artemia franciscana (Latreille), were enriched with erythromycin to determine if Artemia could accumulate therapeutic levels for subsequent feeding to young fish. Three trials were conducted to determine the erythromycin incorporation and survival rates of enriched Artemia when fed either liposomes containing erythromycin or various erythromycin suspensions. Erythromycin concentration in Artemia fed a liposome suspension was low (∼ 5 μg mL −1 ) relative to Artemia fed the direct suspension (> 100 μg mL −1 ) over the same time period. When enriched with suspensions up to 1 g erythromycin L −1 sea water for 14 h, Artemia survival was not significantly affected ( P > 0.05) relative to controls. Using a suspension of 1 g L −1 , tissue erythromycin concentrations of 109 ± 16 μg erythromycin mL −1 Artemia homogenate (mean ± SEM) were achieved after 12 h. Concentrations above 170 μg mL −1 were obtained using suspensions of 2–5 g L −1 , but Artemia survival significantly ( P

Caste differences in feeding and trophallaxis in the western drywood termite, Incisitermes minor (Hagen) (Isoptera, Kalotermitidae) - B. J. Cabrera; M. K. Rust (Insectes Sociaux, 1999)